A case of transitional cell carcinoma of renal pelvis with an extremely high serum carcinoembryonic antigen (CEA) level - Fujii, Y (Hinyokika kiyo. Acta urologica Japonica, 1992)
A case of urothelial tumor with extremely high serum carcinoembryonic antigen (CEA) levels is described. A 68-year-old female presented with macroscopic hematuria and left flank pain. Laboratory examination revealed an extremely high serum level of CEA (194 ng/ml) and elevated levels of serum CA 19-9 (235 U/ml) and squamous cell carcinoma (SCC)-Antigen (10.7 ng/ml), while urine CEA remained within normal limits. No abnormal findings were recognized in gastrointestinal and respiratory systems, but left renal pelvic tumor (T4N2M0) was discovered. Nephroureterectomy with regional lymph node dissection was done. The pathologic anatomy was infiltrating non-papillary transitional cell carcinoma (TCC, G2 = G3, pT4N2M0). More than 30% of the tumor cells were positive for CEA by ABC-peroxidase staining. Levels of tumor markers remained higher than normal after the operation and were normalized after M-VAC (methotrexate, vinblastine, adriamycin and cisplatin) chemotherapy. However, 6 months after the operation, levels of tumor markers rose again and lung metastases appeared. She died 10 months after the operation